Sistem Perencanaan Dan Peramalan Distribusi Produk Berdasarkan Jumlah Permintaan Menggunakan Metode Weight Moving Average - Anindya Palmitraazzah (Faculty of Computer Science, University of Jember, 2017)
Purnama Jati is one of the home industries in Jember Regency which is specialized in Jember specialities food. One of the excellent products produced by Purnama Jati is “proll tape”. To market its products, Purnama Jati has been working with several outlets that are spread in Jember Regency. The uncertainty of the number of the “proll tape” demands cause the number of product distributions with the product necessity of each outlet is not equal, which make the process of product delivery becomes ineffective. One of the effort to anticipate that condition is by building a forecasting system using the method of Weight Moving Average to help the Purnama Jati to predict the distribution of products toward each outlet. Moreover, this system has been built by generating value for each outlet about 71% -76%, and the MAPE value range's from 24% -29% so the planning and forecasting system on the distribution of products is count as an applicable system category.The methods examination is done by comparing the manual calculations and the system calculations. The results obtained are accurate, so the method of calculation on the application are equal to the manual calculation.